DEVELOPMENTS OF ACCOUNTING STANDARDS FOR GOODWILL AND IDENTIFIABLE INTANGIBLES: AN AUSTRALIAN CONTEXT - Shahwan, Yousef (Akutansi Bisnis & Manajemen ( ABM ), 2003)
Accounting for goodwill and identifiable intangibles is one of the most controversial issues in financial reporting. It has been on the agenda of the Australian Accounting Standards Board, the US, UK, and the International Accounting Standards Boards, and the Full High Court of Australia. The Australian Securities and Investments Commission has also placed accounting for intangibles in its Media Releases directed at specif9ic companies. The objective of the present paper is to consider the recent developments of accounting standards for goodwill and identifiable intangibles made by the USA, UK, Canada, and the International Accounting Standards Board (IASB) from one hand. On the other hand, it reviews the historical documents that have been issued since the release of the Australian goodwill standard. Reference to concurrent studies is made to explore the effect of standard developments in promoting uniformity of practice in Australia.